2012
DOI: 10.1186/1471-2164-13-168
|View full text |Cite
|
Sign up to set email alerts
|

AlliumMap-A comparative genomics resource for cultivated Allium vegetables

Abstract: BackgroundVegetables of the genus Allium are widely consumed but remain poorly understood genetically. Genetic mapping has been conducted in intraspecific crosses of onion (Allium cepa L.), A. fistulosum and interspecific crosses between A. roylei and these two species, but it has not been possible to access genetic maps and underlying data from these studies easily.DescriptionAn online comparative genomics database, AlliumMap, has been developed based on the GMOD CMap tool at http://alliumgenetics.org. It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 37 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…The major genetic loci conditioning red bulb colour ( R ) and fructan content ( Frc ) were located on this map by QTL analysis on chromosomes 7 and 8 respectively, as expected [42-44]. This resource is useful across onion germplasm since the anchor markers used here have been tested in other mapping populations, allowing the linkage maps to be aligned for comparative mapping using the CMap tool [45] provided at http://alliumgenetics.org[41]. The map was then used as a reference to select a subset of genotypes for bin mapping [46,47] to facilitate rapid marker screening and targeted map development.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The major genetic loci conditioning red bulb colour ( R ) and fructan content ( Frc ) were located on this map by QTL analysis on chromosomes 7 and 8 respectively, as expected [42-44]. This resource is useful across onion germplasm since the anchor markers used here have been tested in other mapping populations, allowing the linkage maps to be aligned for comparative mapping using the CMap tool [45] provided at http://alliumgenetics.org[41]. The map was then used as a reference to select a subset of genotypes for bin mapping [46,47] to facilitate rapid marker screening and targeted map development.…”
Section: Resultsmentioning
confidence: 96%
“…The overall map length was 808 cM. The map and underlying data can also be accessed at alliumgenetics.org [41]. The markers appeared to show both some overlap at particular positions, which may indicate redundancy or gene clusters but were also spread across the genome with an average spacing between markers of 7.5 cM.…”
Section: Resultsmentioning
confidence: 99%
“…However, the rapid advance in sequencing methodologies and bioinformatics tools means most genome sequencing projects now use shotgun gDNA sequencing or reduced representation sequencing (depending upon the size and complexity of genome) rather than sequencing BACs (Feuillet et al. ). A pilot genome sequencing project employing BAC and whole‐genome shotgun sequencing revealed that onion has one of the lowest gene densities found in plants (1 gene per 168 Kb), and that simple shotgun gDNA sequencing approaches would not be suitable due to large genome size and huge amount of repetitive sequences (Jakse et al.…”
Section: Genomic Resources In Onionmentioning
confidence: 99%
“…An online genomic database has been developed for the Allium genus called Allium Map https://allium.scinet.org.nz/ which consists of genomic data and genetic maps of economically important Allium species (McCallum et al. ). Recently, an onion transcriptome database (http://onion.riceblast.snu.ac.kr/) was created which contains a transcriptome assembly and gene annotations.…”
Section: Genomic Resources In Onionmentioning
confidence: 99%
“…Gene expression is the process by which information from a gene is used in the synthesis of a functional gene product. These products are often proteins, but in non-protein coding genes such as transfer RNA (tRNA) or small nuclear RNA (snRNA) genes, the product is a functional RNA [156][157][158][159][160][161][162]. In onion, the physiology of the bulb beginning was precisely defined by Mettananda and Fordham [163]; photoperiodic conditions mark bulb beginning, similar to the photoperiodic switch of flowering in other species [20,164].…”
Section: Gene Expression and Bulb Enlargementmentioning
confidence: 99%